Tilapia Lake Virus-Induced Neuroinflammation in Zebrafish: Microglia Activation and Sickness Behavior - Mojzesz, Miriam; Widziolek, Magdalena; Adamek, Mikolaj; Orzechowska, Urszula; Podlasz, Piotr; Prajsnar, Tomasz K.; Pooranachandran, Niedharsan; Pecio, Anna; Michalik, Anna; Surachetpong, Win; Chadzinska, Magdalena; Rakus, Krzysztof (Frontiers in Immunology, 2021)
In mammals, the relationship between the immune system and behavior is widely studied. In fish, however, the knowledge concerning the brain immune response and behavioral changes during brain viral infection is very limited. To further investigate this subject, we used the model of tilapia lake virus (TiLV) infection of zebrafish (Danio rerio), which was previously developed in our laboratory. We demonstrated that TiLV persists in the brain of adult zebrafish for at least 90 days, even when the virus is not detectable in other peripheral organs. The virions were found in the whole brain. During TiLV infection, zebrafish displayed a clear sickness behavior: decreased locomotor activity, reduced food intake, and primarily localizes near the bottom zone of aquaria. Moreover, during swimming individual fish exhibited also unusual spiral movement patterns. Gene expression study revealed that TiLV induces in the brain of adult fish strong anti-viral and inflammatory response and up-regulates expression of genes encoding microglia/macrophage markers. Finally, using zebrafish larvae, we showed that TiLV infection induces histopathological abnormalities in the brain and causes activation of the microglia which is manifested by changes in cell shape from a resting ramified state in mock-infected to a highly ameboid active state in TiLV-infected larvae. This is the first study presenting a comprehensive analysis of the brain immune response associated with microglia activation and subsequent sickness behavior during systemic viral infection in zebrafish.